Emotional contagion in dyadic online video conferences—empirical evidence based on self-report and facial expression data - Marx, Anton K. G.; Sachs, David F.; Frenzel, Anne C.; Schweizer, Martin T. (Frontiers in Psychology, 2025)
IntroductionEmotional contagion is an essential and prevalent emotional process in social interaction and comprises the transmission of emotions between two or more individuals. The vast majoriy of prior research explored the emotional contagion in face-to-face human interaction. The present study explored the degree to which emotional contagion occurs in dyadic online video conferences, using subjective self-report and automatically coded facial expression data.MethodsIn a lab-based experimental approach, 104 participants (in 52 dyads) interacted via synchronized computers. They were prompted to talk to each other about recent personally relevant experiences that made them angry, happy, and sad (3 conditions). We recorded participants’ emotions by means of automated facial expression analysis and retrospective self-report after each condition.ResultsOur preregistered analyses provided evidence for emotional contagion of all three emotions during the video conferences based on the self-report data. Regarding facially expressed emotions, only joy seemed to be transmitted, while the frequency of facially expressed anger and sadness was generally very low, and did not differ across conditions. We further explored temporal co-occurrences of facially expressed joy through cross-recurrence quantification analysis. Those results showed that both interaction partners’ facial expressions of joy, but not of anger and sadness, co-occurred significantly above chance.DiscussionOverall, we conclude that emotions can be transmitted across interaction partners during online video interactions, but the face does not seem to be the key channel for those contagion processes, particularly not for negative emotions.